Reclamation Status of Soils in Konimex Natural-Geographical Region - Axmedovna, Qilichova Nazokat (American Journal of Biology and Natural Sciences, 2026)
This article analyzes the salinity levels, chemical properties, and dynamics of changes in automorphic, semi-hydromorphic, and hydromorphic soils in Konimeh district of Navoi region between 2015 and 2023. As a result of the research,the results showed that under the influence of irrigation and leaching, a desalination process occurred, and salts accumulated in the lower 100-200 cm layers. However, it is established that this process does not negatively affect the growth and development of agricultural crops.